Effects of food-chain mediated metal exposures on phosphatases’ profile in rats - Ovie, Richard; Asagba, Samuel (International Journal of Pharmacology and Toxicology, 2016)
This study seeks at investigating the separate and combined toxicities of Arsenic (As) and Cadmium (Cd) administered along food-chain. The natural food-chain was mimicked by exposing rats to diet containing milled Cd and As-exposed (at a dose of 0.4mg/100ml each) catfish as source of protein. Control groups were fed with normal formulated rat feed with non-metal contaminated fish as source of protein. The effects of Cd and As exposures were sought by determining indices of plasma and lysosomal membrane integrity in plasma and organs of the rats after three months exposure time. The results depict that Cd and As exposures in the rats led to bioaccumulation of the metals in their plasma and organs. The results gotten revealed significance (p<0.05) in gain of body weight in both Cd and As exposed rats when control is compared to them. Phosphatases’ activities (ALP and ACP) in the plasma and vital organs were also significant in the metal inoculated rats when the control is compared to them. These results explained that arsenic and cadmium forms free radicals which cause stress due to oxidation, kidney impairment and immunologic disorders.